Microsimulation approaches to studying shocks and social protection in selected developing economies - Kwabena Adu-Ababio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper calculates automatic stabilization in Ghana, South Africa, and Ecuador to explain income cushioning amid income and demand shocks. Fiscal policies within these countries are also stress tested to gauge welfare contingencies and insurance. A discretionary action approach is adopted for Ghana as it fails shock resistance tests by introducing additional safety nets that improve welfare. For the three countries, income stabilization ranges from 1 to 22 per cent while demand stabilization ranges from 4 to 25 per cent. Ranging from nil to 46 per cent, a new concept of poverty stabilization is formalized to measure vulnerability. Results from the study reveal how the existing social policy structure cushions households.
Keywords: H20; H31; H53; O12; 330; developing countries; shocks; social protection; fiscal policy; microsimulation